Creation of 3D terahertz photonic crystals by the direct writing technique with a TiO2 sol‐gel ink. Issue 5 (4th December 2017) - Wang, Rong; Yang, Weiyi; Zhu, Pengfei; Gao, Shuang; Li, Bo; Li, Qi
Abstract: Three‐dimensional TiO2 woodpile terahertz photonic crystals with feature size less than 100 μm were created by the direct writing technique with a TiO2 sol‐gel ink. With proper heat treatment, the rheological properties of the TiO2 sol‐gel ink were modulated to meet the requirement to construct 3D‐TPCs with feature size less than 100 μm by the direct writing technique. Well‐crystallized rutile TiO2 3D‐TPCs were obtained by the calcination process to provide the required high refractive indices, while the lattice periods of these TiO2 3D‐TPCs could be changed to tune their terahertz properties. With the increase of the lattice period, a shift of their THz photonic band gap peaks toward the lower frequency was observed in both the simulated and experimental investigations.